Markets and structural studies: MSSD research themes brochure - International Food Policy Research Institute (International Food Policy Research Institute, 2001)
Inadequate policies, institutions, and rural infrastructure lead to agricultural markets that do not function efficiently. As a consequence, the poor pay more for their food and receive less for their produce. To enhance the efficiency of markets, and support their development, the Market and Structural Studies Division analyzes agricultural market reforms, crop and income diversification, postharvest activity, and agroindustry. Countries moving from a subsistence or centrally controlled economy to a commercial market-oriented economy face a difficult period of transition. This transition is typically accompanied by changes in product mix, sources of income, the structure of employment and the productivity of labor. The prospects for reducing rural poverty, assuring food security, and improving rural livelihoods depend on how governments manage this change. The Markets and Structural Studies Division seeks to understand how countries can best develop markets, institutions and infrastructure in ways that contribute to agricultural growth, help alleviate poverty and ensure food security for all.